Decreased H3K9ac level of AT2R mediates the developmental origin of glomerulosclerosis induced by prenatal dexamethasone exposure in male offspring rats. (1st January 2019) - Li, Bin; Zhu, Yanan; Chen, Haiyun; Gao, Hui; He, Hangyuan; Zuo, Na; Pei, Linguo; Xie, Wen; Chen, Liaobin; Ao, Ying; Wang, Hui
Abstract: This study aimed to demonstrate that prenatal dexamethasone exposure (PDE) can induce kidney dysplasia in utero and adult glomerulosclerosis in male offspring, and to explore the underlying intrauterine programming mechanisms. Pregnant rats were subcutaneously administered dexamethasone 0.2 mg/kg.d from gestational day (GD) 9 to GD20. The male fetus on GD20 and the adult offspring at age of postnatal week 28 were analyzed. The adult offspring kidneys in the PDE group displayed glomerulosclerosis, elevated levels of serum creatinine and urine protein, ultrastructural damage of podocytes, the reduced expression levels of podocyte marker genes, nephrin and podocin. The histone 3 lysine 9 acetylation (H3K9ac) level in the promoter of renal angiotensin II receptor type 2 (AT2R) and its expression were reduced, whereas the angiotensin II receptor type 1a (AT1aR)/AT2R expression ratio was increased. The fetal kidneys in the PDE group displayed an enlarged Bowman's space and a shrunken glomerular tuft, a reduced cortex width and an increase in the nephrogenic zone/cortical zone ratio, reduced the expression level of glial-cell-line derived neurotrophic factor/c-Ret tyrosine kinase receptor (GDNF/c-Ret) signal pathway and podocyte marker genes. Moreover, the H3K9ac and H3K27ac levels of AT2R as well as the gene and protein expression levels of AT2R in fetal kidneys were inhibited by PDE. In vitro, primary metanephric mesenchyme stem cells (MMSCs) were treated with dexamethasone. Overexpression of AT2R reversed the inhibited expression of GDNF/c-Ret and podocin/nephrin induced by dexamethasone, and glucocorticoids receptor antagonist abolished the decreased H3K9ac level and gene expression of AT2R. In conclusion, PDE induced the offspring's kidney dysplasia as well as adult glomerulosclerosis, which was mediated by a sustained decrease in renal AT2R expression via decreasing the H3 K9ac level.